Artificial Intelligence Development in Large Technology Companies: A System Review - Zavaleta Galarza, Erick Arnie (2026)
The development of Artificial Intelligence (AI) in large technology companies was analyzed through a systematic review with the aim of identifying the main areas of application, the products and solutions developed, and their impact on the competitiveness and sustainability of industries. The methodology included the collection and analysis of relevant information on companies such as Amazon, Microsoft, Alphabet and IBM, highlighting their technological innovations and implementation strategies. The results revealed that sectors such as finance, health and telecommunications concentrate the most frequent applications of AI, allowing for the optimization of processes, improved decision-making and personalization of products and services. In addition, key solutions such as Azure AI, Watsonx and Vertex AI were identified, which have driven the transformation of various industries. It was also observed that AI has promoted sustainability by optimizing resources and mitigating environmental risks, as well as social inclusion by eliminating linguistic and cultural barriers. On the other hand, it is crucial to identify challenges related to technological limitations and the need to combine automation with human interaction to ensure satisfactory experiences.